عائلی مسئلہ (منگیترکو دیکھنا )کے بارے میں ابن تیمیہؒ اور جمہور فقہاء کےاختلاف کا تقابلی جائزہ: A Comparative Study of Ibn Taymiyyah and the Consensus of Jurists on the Issue of Viewing the Fiancée - Mamoona Islam; Dr.Feroz u din Shah (International Research Journal of Arabic and Islamic Studies, 2024)
Marriage is the only means of legal union between a man and a woman for the purpose of human reproduction, and it is a matter established by every religion and nation of the world. There is guidance in Islam about looking at a woman before marriage. According to Imam Ibn Taymiyyah, the fiancee cannot be seen in any case before marriage. While the Islamic scholars have denied it and have gone towards its justification. There are many arguments in the sources and basic books of Islamic teachings which have clearly supported the justification of this practice. And it seems logically correct that until the woman and the man at least look at each other and are satisfied, this process remains unfinished. A comparison has been made and the opinions of both of them have been resolved in the light of Shariah statements. Nowadays, it is very important to talk about this issue so that practice of uncivilized ways while arranging marriages in families and lawlessness ends and hence the series of legal marriages can start in the society within nations.